Clinico-Biochemical and Nephroprotective Effects of Medicinal Herbs on Gentamicin Induced Nephrotoxicity in Wistar Rats - Vagh, A.A.; Patel, R.M.; Mavadiya, S.V.; Mehta, S.A.; Khasatiya, C.T.; Vala, J.A.; Parmar, S.M.; Varia , R.D. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Nephrotoxicity followed by kidney disease is the main complication of gentamicin treatment. Medicinal plants and herbs have played an important role in the prevention and treatment of kidney diseases. With this concern the ethanol extract of Zingiber officinale rhizomes, ethanol extract of Tinospora cordifolia roots and methanol extract of Cajanus indicus leaves were compared for their nephroprotective effect in the Wistar rats. A total of 48 Wistar rats were distributed into six equal groups (n=8) and were exposed to gentamicin sulphate @ 100 mg/kg orally for 7 days to induce nephrotoxicity in 5 groups. Group G1 was kept as healthy control and group G2 was considered as untreated induced nephrotoxic control, whereas the rats of groups G3, G4, G5 and G6 were given, along with gentamicin sulphate @ 100 mg/kg, extracts of Zingiber officinale @ 400 mg/kg b.wt, Tinospora cordifolia 200 mg/kg b.wt, Cajanus indicus @ 400 mg/kg b.wt and syrup Cystone @ 500 mg/kg b.wt., respectively, orally for 7 consecutive days as neproprotective drugs. A significant (P
Keywords: Gentamicin; Nephrotoxicity; Zingiber officinale; Tinospora cordifolia; Cajanus indicus; Nephroprotection